Pyrazole Containing Morpholine Moiety Compound: Bridging Experiment and Theoretical Investigation through Spectroscopy and Quantum Methods with Special Reference to NLO and Molecular Docking Insights - Bavani, C.; Pritha, Periyasamy; Kishore, Govindarajalu; Bhakiaraj, D.; Xavier, S.; Sebastian, S. (Asian Journal of Chemistry, 2025)
The current study carefully explores the spectroscopic and molecular structural studies of 4-(4,5-dihydro-3-(4-morpholinophenyl)-1H-pyrazol-5-yl)-N,N-dimethylbenzenamine (DMH). Theoretical calculations were computed at the B3LYP functional and 6-311G(d,p) basis set, which was compared with experimental UV-vis and FT-IR investigations. The donor-acceptor interactions of the DMH molecule were ascertained using the natural bond orbital (NBO). The mode of vibration was identified using the potential energy distribution (PED). An adaptation of the gauge independent atomic orbital (GIAO) method was used to assess the 1H and 13C NMR. The electronic transition of the molecule was confirmed using the time-dependent density functional theory (TD-DFT) approach. All the spectral analyses were compared theoretically and experimentally to bolster the goal of the findings. The theoretical band gaps were also predicted to be 4.26 eV, a vast energy gap suggesting the stability of the compound. In order to investigate the active area, the charge distribution and molecular electrostatic potential of DMH molecule were also investigated. Furthermore, the molecular docking was performed against three different proteins to examine the inhibition rate of the synthesized molecule.